Hepatogenous photosensitization by Brachiaria spp. in sheep: first report in Mexico - Montoya-Ménez, Celic B.; Ruíz-Ramírez, Johnatan A.; Márquez, Luis J. G.; Méndez-Bernal, Adriana; Morales-Salinas, Elizabeth; Ramírez-Romero, Rafael; Martínez-Burnes, Julio; López-Mayagoitia, Alfonso (Brazilian Journal of Veterinary Pathology, 2019)
Ruminants are highly susceptible to photosensitization caused by the ingestion of hepatotoxic plants. In two adjacent farms in Colima, Mexico, several sheep exhibited signs of depression and crusting dermatitis involving the ears, periorbital skin, eyelids, nostrils, and axillary regions. Results of serum biochemistry were indicative of liver injury. Post mortem examination revealed jaundice, craniofacial edema as well as an enlarged liver having an orange-brown discoloration; on the cut surface, the hepatic parenchyma had a subtle zonal pattern. Histopathological findings were those of severe necrotizing dermatitis, lymphoplasmacytic cholangiohepatitis, and renal tubular necrosis. Acicular crystals were microscopically and ultrastructurally evident in hepatocytes, Kupffer cells, biliary ducts, renal tubules and interstitium. The clinical, gross and microscopic findings were consistent with hepatogenous photosensitization. A field investigation revealed that affected sheep had been grazing Brachiaria spp., a potentially toxic grass originated from Africa and commonly cultivated in Australia and South America. This grass contains hepatotoxic saponins that cause liver injury and secondary hepatogenous photosensitization. Although frequently reported in South America, to our knowledge, this is the first report of Brachiaria spp. toxicity in Mexico.